Peer-led Aboriginal parent support: Program development for vulnerable populations with participatory action research - Munns, Ailsa; Toye, Christine; Hegney, D.; Kickett, M.; Marriott, R.; Walker, R. (eContent Management, 2017)
Background: Participatory action research (PAR) is a credible, culturally appropriate methodology that can be used to effect collaborative change within vulnerable populations. Aim/objective: This PAR study was undertaken in a Western Australian metropolitan setting to develop and evaluate the suitability, feasibility and effectiveness of an Aboriginal peer-led home visiting programme. A secondary aim, addressed in this paper, was to explore and describe research methodology used for the study and provide recommendations for its implementation in other similar situations. Methods: PAR using action learning sets was employed to develop the parent support programme and data addressing the secondary, methodological aim were collected through focus groups using semi-structured and unstructured interview schedules. Findings were addressed throughout the action research process to enhance the research process. Results: The themes that emerged from the data and addressed the methodological aim were the need for safe communication processes; supportive engagement processes and supportive organisational processes. Conclusions: Aboriginal peer support workers (PSWs) and community support agencies identified three important elements central to their capacity to engage and work within the PAR methodology. This research has provided innovative data, highlighting processes and recommendations for child health nurses to engage with the PSWs, parents and community agencies to explore culturally acceptable elements for an empowering methodology for peer-led home visiting support. There is potential for this nursing research to credibly inform policy development for Aboriginal child and family health service delivery, in addition to other vulnerable population groups. Child health nurses/researchers can use these new understandings to work in partnership with Aboriginal communities and families to develop empowering and culturally acceptable strategies for developing Aboriginal parent support for the early years. Impact Statement Child health nurses and Aboriginal communities can collaborate through participatory action research to develop peer-led support for the early years. Indigenous Australian peoples are people who identify as Aboriginal or Torres Strait Islander. Respectfully, throughout this paper, they will be described as Aboriginal.